Efektivitas Layanan Bimbingan Kelompok dengan Teknik Sosiodrama terhadap Perilaku Cyber bullying pada Remaja - Puspita, Elina Ayu; Jahju Hartanti; Elia Firda Mufidah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
This study aims to examine the effectiveness of group counseling services using the sociodrama technique to overcome cyber bullying on social media. This study used a quantitative approach with the One Group Pretest and Posttest Design. The sample consisted of 7 Grade VIII students of SMP Wachid Hasyim 10 Prambon and the samples were taken through purposive sampling. The results of the Wilcoxon Non-Parametric Test showed an increase in the pre-test and post-test on students with significance results showing 0.018 <0.05. It can be concluded that H0 is rejected and Ha is accepted. So it can be concluded that group guidance services using the sociodrama technique are effective in reducing cyber bullying behavior.